Insanity and sanctity in Byzantium - Rotman, Youval. (Cambridge, Massachusetts)
256 sayfa
Keywords: “Insanity and Sanctity in Byzantium aims to understand how the use of psychological abnormality functions in deep societal transformations, producing a major shift in the religious, cultural, mental, and social aspects. The book examines a particular set of religious phenomena, in a broadly defined period and area - the Eastern Mediterranean and the Near East between the birth of Christianity and that of Islam - and seeks to reach conclusions on the nature and function of abnormal behavior sanctified by society. Taking as a starting point a particular type of saint of Orthodox Christianity, the holy fool, the person who feigns madness, and investigating other types of saints who portray abnormal behavior, such as the martyr and the ascetic, the book reveals the ambiguous character of the boundary between sanity and insanity. It explains the significance of this ambiguity to the religious experience as a motor of social movement, and sets it at the core of the socio-religious transformation that changed the Antique civilization into a world of medieval societies.“--